Lessons Learned from a Smart City Project with Citizen Engagement - Ernst, Sebastian; Zaworski, Konrad; Sokołowski, Piotr; Salwa, Grzegorz (Wydawnictwo Politechniki Łódzkiej, 2023)
The paper discusses the experiences gained in a joint research project by AGH and the commune of Siechnice. Two main areas are discussed: collecting data from heterogenous sensor devices as well as input from citizens, and development of analytic procedures in a way which guarantees integration between day-to-day and research operations. The most prominent outcomes of the project include the development of a living lab as well as automation of multi-aspect inference, which would normally have to be carried out by a team of experts.
Keywords: smart cities; data analysis; citizen engagement; inteligentne miasta; analiza danych; zaangażowanie obywateli